IoT Based Monitoring Device (Gas Leakage) - Selvaraj, Mohamad Daniel Bin Mohd; PN. MARDZULLIANA BINTI ZULKIFLI (Progress in Engineering Application and Technology, 2021)
A IoT based monitoring device which measures and senses gas that also alerts the users through mobile devices.This paper represents based on graduation project; a simulation and prototype in which when there is gas leakage occur, using a Wi-Fi as medium of transferring date the gas sensor alerts the user’s mobile devices using a Wi-Fi module with the help of Blynk app. We have used various components in this project such as NodeMcu, gas sensor (MQ-2), buzzer, Blynk app. All these components can be monitor by the Blynk app. The aim of this project is to increase response time, increase efficient in F&G system, prioritize safety and hazard protocols. Firstly, we release gas to the gas sensor, then the gas sensor will send information to NodeMcu and initiates data transferring to Blynk app on the mobile devices, which then will be monitored through it. The first author will mainly be carrying out designing, implementation and analysis of “IoT based monitoring device (gas leakage)”.